Critical Evaluation of Performance Assessment Implementation in Secondary Schools Biology Learning: Meta-Analysis Study - Nur Rohmah, Lulu; Bidayati Haka, Nukhbatul; Oktina Sari Pratama, Anisa (Universitas Tidar, 2025)
Biology learning in secondary schools still faces various challenges, particularly related to poor conceptual understanding, limited scientific skills, and declining student motivation. One major issue is the dominance of conventional assessment techniques that emphasize memorization rather than demonstrating real ability through performance. This study aims to determine the magnitude of the influence of the use of performance assessment in biology learning in secondary schools by considering moderator variables such as geographic area, teaching materials, and implementation success. The study was conducted based on the PRISMA guidelines for systematic reviews and meta-analyses, and used JASP-0.19.3.0 software for data analysis. The results showed that performance assessment has a statistically significant influence on biology learning with a medium effect size on the variables of geographic area (0.585), teaching materials (0.552), and implementation success (0.552). These findings confirm that the use of performance assessment contributes positively to improving students’ conceptual mastery, scientific skills, and learning motivation. Therefore, performance assessment can be recommended as a relevant and effective evaluation strategy to overcome the limitations of traditional assessments and improve the quality of biology learning in secondary schools.